Implementasi Pembatasan Akses Sosial Media Menggunakan Layer 7 Protocol Pada Perangkat Mikrotik DI SMK IDN - Abdul Shomad; Yuma Akbar; Dadang Iskandar Mulyana (INFORMATICS FOR EDUCATORS AND PROFESSIONAL : Journal of Informatics, 2022)
: SMK IDN Borading School is one of the schools in Bogor Regency that has national standards. This school has a very broad environment. In addition, this school also has a fairly good internet network. This can be seen by the breadth of the internet network that almost covers the entire school environment. At SMK IDN, the main problem is the use of internet network data by students to play games and social media during study hours, so it takes a system that is capable of being a protection so that users cannot use the internet to play games and social media during study hours. . Based on this, this study aims to test the implementation of social media access restrictions using the layer 7 protocol feature on a network with Mikrotik devices at SMK IDN. In general, this study shows the success of blocking several social media applications such as youtube, instagram and tiktok. So when social media like the one above can be blocked learning in class will be very conducive where students will always pay attention to the teacher who is delivering material and students will not be able to steal opportunity to access social media in class.